2002
DOI: 10.1002/1521-4117(200204)19:1<47::aid-ppsc47>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Numerical Studies Characterizing Optical Properties of Soot Aggregates for Improved EXSCA Measurements

Abstract: In order to compare EXSCA measurements with light‐scattering calculations, numerical studies characterizing the optical properties of soot aggregates were compared by using different approaches: [1] the Rayleigh‐Debye‐Gans theory for the fractal aggregate model (RDG‐FA), studied by Faeth and Köylü, [2] the rigorous solution model (RS) proposed by Xu, and [3] the discrete dipole approximation model (DDA), developed by Draine and Flatau. The extinction, absorption and scattering cross‐sections, C$\rm{ {_{e}^{a}}… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
(39 reference statements)
2
19
0
Order By: Relevance
“…GMM was developed by Xu (1995Xu ( , 1997 based on the framework of the Mie theory for a single sphere and the addition theorems for spherical vector wave functions. It provides a rigorous and complete solution to nonoverlapping multisphere light scattering problems and can be readily applied to fractal soot aggregates ( Van-Hulle et al 2002;Liu and Snelling 2008). Execution of this numerically exact method requires the positions, diameter, and refractive index of each constituent sphere (primary particle).…”
Section: Generalized Mie-solution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GMM was developed by Xu (1995Xu ( , 1997 based on the framework of the Mie theory for a single sphere and the addition theorems for spherical vector wave functions. It provides a rigorous and complete solution to nonoverlapping multisphere light scattering problems and can be readily applied to fractal soot aggregates ( Van-Hulle et al 2002;Liu and Snelling 2008). Execution of this numerically exact method requires the positions, diameter, and refractive index of each constituent sphere (primary particle).…”
Section: Generalized Mie-solution Methodsmentioning
confidence: 99%
“…Execution of this numerically exact method requires the positions, diameter, and refractive index of each constituent sphere (primary particle). Although CTM has become the most popular method to study the radiative properties of various scatterers , GMM has also been demonstrated to be a powerful tool to study radiative properties of various particles (Xu 1995(Xu , 1997Van-Hulle et al 2002;Liu and Snelling 2008). In fact, CTM and GMM share a very similar theoretical framework, though differences exist (Xu and Khlebtsov 2003).…”
Section: Generalized Mie-solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RDG-FA theory has been introduced by Köylü and Faeth [6,13] and its validity has been checked by comparison with more accurate formulations [15,16]. However the main difficulty of the application of the above relations is that the complex refractive index m value of soot particles has to be known.…”
Section: Dimensionless Soot Extinction Coefficient K Ementioning
confidence: 99%
“…Xu (1995Xu ( , 1996Xu ( , 1997 and Xu and Gustafson (2001) continued the development to produce what is known as the GMM method to deal with aggregates of arbitrary size and configuration, formed from monomers that are homogeneous spheres of possibly different radii and compositions. This GMM method was recently used to calculate the singlescattering properties of fractal aggregates by Van-Hulle et al (2002), Liu and Smallwood (2010, 2011), and Li et al (2010. By replacing the Lorenz-Mie theory for homogeneous particles with the core-mantle Mie theory, i.e., providing the amplitude coefficients given by the core-mantle Mie theory, the GMM was extended to compute the scattering properties of the aggregates with coated inhomogeneous monomers (Xu and Khlebtsov 2003).…”
Section: Introductionmentioning
confidence: 99%